Overexpression of toll-like receptor 9 correlates with podocyte injury in a murine model of autoimmune membranoproliferative glomerulonephritis - Md. Abdul Masum; Osamu Ichii; Yaser Hosny Ali Elewa; Teppei Nakamura; Yuki Otani; Marina Hosotani; Yasuhiro Kon (Autoimmunity, 2018)
Toll-like receptors (Tlrs) are sensors of danger signals which promote the activation of immune cells and intrinsic renal cells. Podocytes, the intrinsic cells of glomerulus, are continuously exposed to various plasma solutes and danger signals due to their unique location in the glomerulus. Herein, we show that Tlr9 is overexpressed in podocytes and the mechanisms which cause its injury and development of membranoproliferative glomerulonephritis (MPGN) in model BXSB/MpJ-Yaa (Yaa) mice. Yaa mice developed typical lesions of MPGN and showed strong expression of Tlr9 mRNA throughout the glomerulus particularly toward the periphery of the glomerulus. However, BXSB/MpJ (BXSB) mice showed no lesion for MPGN but a very weak expression of Tlr9 mRNA. Relative mRNA expression of Tlr9 and its downstream cytokines, including interleukin 1 beta (Il1b), Il6, interferon gamma (Ifng) and tumour necrosis factor alpha (Tnfa) was markedly increased in glomeruli isolated from Yaa mice. Tlr9 protein expression was almost absent in BXSB mice but intense expression was found in Yaa mice. Podocyte protein expression was normal in BXSB mice but decreased in Yaa mice and colocalized with Tlr9 protein. Furthermore, electron microscopy examination revealed podocyte injury and electron-dense materials in thickened glomerular basement membrane of Yaa mice. Glomerular Tlr9 mRNA expression was significantly correlated with anti-dsDNA antibody, proteinuria, renal function indices (sBUN and sCr), glomerular histopathology indices, downstream factors of Tlr family (Ilb and Tnfa), podocyte injury parameters (p < .05 and p < .01). In conclusion, overexpression of TLR9 correlates with podocyte injury and development of MPGN.